(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Twenty mercury (II) complexes of the type [HgX2L1-10] (Where X=Cl or Br and L1-10 = macrocyclic ligands derived from thiodiglycolic acid and different aliphatic diamines) have been synthesised and characterized by elemental analysis, molar conductivity, IR and XPS data. An octahedral geometry was established for each complex. The ligand molecule and its derivatives were the subject of a drug likeness investigation, which revealed the drug-like character of thiodiglycolic acid. When two protein receptors, 4c6i, 6hfn, 4c61, and 4bqu, were studied using molecular docking, binding energies of -5.7, -5.2, -5.4, and -4.5 Kcal/mol were discovered. These binding energies suggested possible medical applications. Future research on pharmacological agents based on thiodiglycolic acid may benefit from the study.